Sustainable Religious Tourism Product Development and the Mediating Role of Tourist Satisfaction - Khadka , Bhim Bahadur (Journal of Entrepreneurship & Management Studies, 2025)
The sustainable development of religious tourism products increasingly requires the delicate integration of tangible infrastructure with intangible spiritual values; however, the mechanisms linking site attributes to sustainability remain insufficiently examined. This study addresses this gap by investigating how attraction, accessibility, and spiritual atmosphere influence sustainability outcomes, with tourist satisfaction conceptualized as a mediating mechanism. A correlational research design and quantitative approach were employed, using structural equation modeling (SEM) to analyse variable relationships. Data were collected through a purposive sampling survey at six religious sites in Nepal. Of the 600 distributed questionnaires, 483 valid responses were retained after removing incomplete entries and outliers. Findings reveal that attraction and accessibility affect sustainability only indirectly via tourist satisfaction, whereas spiritual atmosphere exerts a distinctive direct effect that bypasses satisfaction. On this basis, the study advances a dual-pathway model of sustainability: one mediated by satisfaction and another driven by spirituality. Theoretically, the study refines expectancy-disconfirmation theory by demonstrating the mediated influence of site attributes, while extending Butler's Tourist Area Life Cycle (TALC) model to foreground spiritual dynamics in sustainability discourse. Practically, the findings highlight the necessity for destination managers to adopt a dual strategy that simultaneously strengthens infrastructure and accessibility while safeguarding spiritual ambience and cultural authenticity as pillars of long-term sustainability. Future studies should broaden geographic scope, integrate mixed-methods designs, and incorporate variables such as cultural attachment, perceived value, and destination image to further enrich sustainability models in religious tourism.